Activation and Radioactive Waste Analysis for Survey X-Ray Crystal Spectrometer of ITER. (17th February 2017) - Subhash, P. V.; Indauliya, Gunjan; Chaitanya, T. Sai; Kanth, Priti; Jakhar, S.; Varshney, Sanjeev; Kumar, Siddharth; Krishna, Raja; Bhaliya, Nirav; Mishra, Sapna; Shrishail, P.; Kumar, Vinay
Abstract : Activation and radioactive waste analysis has been carried out for an X-ray crystal survey spectrometer (XRCS) sight tube, which will be installed in equatorial port No. 11 assigned for the ITER diagnostics. The neutron transport calculations are performed using the Monte Carlo N-Particle code (MCNP). The base C-Lite neutronics ITER model is grossly modified to include all required details of the port plug, diagnostic apertures, and diagnostic system. The transport results provide neutron flux at desired positions. The sight tube is supposed to be placed in the interspace, after the closure plate, to channel X-rays to the spectrometer. Complete radioactive inventory calculations along with contact doses and nuclear activity levels are obtained for two different kinds of sight tube material. FISPACT-2007, an inventory code, is used for this purpose. The analysis for this particular sight tube can be used to obtain a material preference based on a radiation point of view. Further, the dependence of neutron spectrum and irradiation time on activity levels, contact dose rate, and production of dominant dose contributing radionuclides has been studied. Dominant radionuclides that contribute up to 95% of the total dose are identified, and their pathways are generated to back trace their sources as an effort to reduce the dose rate. The effect of reducing the cobalt content in SS316L(N)-IG on the contact dose rate is evaluated separately for the sight tube of the XRCS system. Many of the FISPACT calculations are repeated with ACTYS, a locally developed activation solver.